2009
DOI: 10.1152/ajpgi.00112.2009
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-independent contraction of longitudinal ileal smooth muscle is potentiated by a zipper-interacting protein kinase pseudosubstrate peptide

Abstract: Ca 2ϩ -independent contraction of longitudinal ileal smooth muscle is potentiated by a zipper-interacting protein kinase pseudosubstrate peptide. Am J Physiol Gastrointest Liver Physiol 297: G361-G370, 2009. First published June 18, 2009 doi:10.1152/ajpgi.00112.2009.-As a regulator of smooth muscle contraction, zipper-interacting protein kinase (ZIPK) can directly phosphorylate the myosin regulatory light chains (LC20) and produce contractile force. Synthetic peptides (SM-1 and AV25) derived from the autoinhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 31 publications
0
18
1
Order By: Relevance
“…We showed previously that Ca 2ϩ -independent, microcystin (phosphatase inhibitor)-induced contraction of Triton-skinned rat caudal arterial smooth muscle strips is not blocked by pretreatment with AV25, suggesting that ZIPK activity is not required for the observed Ca 2ϩ -independent contraction or LC 20 diphosphorylation (17). In the case of Triton-skinned ileal smooth muscle strips, however, more recent studies have revealed contractile potentiation and possible activation of ZIPK upon the addition of the AV25 peptide (33). Unexpected variability in the effects of peptide inhibitors in situ, therefore, limits their usefulness in identifying substrates of ZIPK.…”
mentioning
confidence: 92%
“…We showed previously that Ca 2ϩ -independent, microcystin (phosphatase inhibitor)-induced contraction of Triton-skinned rat caudal arterial smooth muscle strips is not blocked by pretreatment with AV25, suggesting that ZIPK activity is not required for the observed Ca 2ϩ -independent contraction or LC 20 diphosphorylation (17). In the case of Triton-skinned ileal smooth muscle strips, however, more recent studies have revealed contractile potentiation and possible activation of ZIPK upon the addition of the AV25 peptide (33). Unexpected variability in the effects of peptide inhibitors in situ, therefore, limits their usefulness in identifying substrates of ZIPK.…”
mentioning
confidence: 92%
“…The pathway downstream of Rho kinase involves activation of ZIP kinase, a Ca 2ϩ -independent MLC kinase, and phosphorylation of the myosin phosphatase targeting subunit, MYPT1, resulting in inhibition of the catalytic subunit of MLC phosphatase. Phosphorylation of MLC 20 by ZIP kinase and inhibition of MLCP result in sustained muscle contraction (4,23,36). The pathway in circular smooth muscle, as previously shown, involves sequential activation of G q and/or G 13 , p115 RhoGEF, and RhoA (20,37,38,41,42).…”
Section: Discussionmentioning
confidence: 78%
“…The signaling pathway involves sequential activation of G␣ 13 , p115RhoGEF, RhoA/Rho kinase, and RhoA/PKC leading to inhibition of MLCP upon phosphorylation of its regulatory subunit, MYPT1 by Rho kinase, and phosphorylation of CPI-17, an endogenous inhibitor of MLCP, by PKC (4,41,42). ZIP kinase is activated downstream of Rho kinase and induces sustained MLC 20 phosphorylation and muscle contraction enhanced by a low ambient MLCP activity (23,36).In contrast, contraction of intestinal longitudinal smooth muscle is initiated by a distinct signaling pathway. Ca 2ϩ mobilization in longitudinal muscle is mediated by activation of cytosolic phospholipase A 2 (cPLA 2 ) and generation of arachidonic acid (AA), leading to Ca 2ϩ influx and stimulation of cyclic ADP ribose (cADPR) (30,31,39).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because P0 and adult ileum exhibit a similar dependence of force decline on MLC 20 dephosphorylation, relaxation may largely depend on MLCP activity without excluding the possibility that it is further rate limited by myosins with a slow rate of cross-bridge detachment such as NM myosin II (20,25) or slow SM myosin II isozymes, the latter being expressed in adult tonic SM (35) and possibly also in P0 ileum. The lower expression level of MLCK does not necessarily imply a lower MLCK/MLCP activity ratio as the specific activity of MLCK may be upregulated like in fetal carotid arteries (36) and a high Ca 2+ sensitivity may be supported by Ca 2+ independent MLC kinases (37). Their involvement in the P0 ileum remains to be determined.…”
Section: Properties Of the Contractile Machinerymentioning
confidence: 99%